The homosexuals’ right to procreation in Greece - Κηπουρίδου (Kalliopi Kipouridou), Καλλιόπη; Μηλαπίδου (Maria Milapidou), Μαρία (Bioethica, 2015)
During the last decades there has been a change of attitude regarding the recognition of homosexual rights that is also reflected on their claims for recognition of their right to access to Medically Assisted Reproduction (MAR) or adoption. Although the Greek legislator has shown some signs of progressiveness by adopting laws that ensure the homosexuals’ rights, they have chosen not to include the homosexual couples in the l. 3719/2008 regarding civil partnership. In Greece, discussions concerning the integration of homosexuals in the civil partnership had already commenced during the vote of the relevant law. This discussion has revived after the conviction of our country by the ECHR in the case of Vallianatos and Others vs Greece. For the time being, however, the legal situation in Greece, as far as the homosexuals’ access to MAR or adoption is concerned, entails the following conclusions. Firstly, although the legal right to procreation is established in article 5 §1 of the Constitution, reality differs for homosexuals and especially for homosexual couples in Greece, which do not have access to MAR methods. It is quite common, in practice, for one of the members of a lesbian couple with fertility problems to visit a doctor as a single woman and gain access to MAR methods. On the contrary, homosexual men do not have any chance of having access to MAR methods either as single men or as a couple. Regarding the homosexuals’ access to adoption, Articles 1452 et seq. Civil Code make no specific reference either to the adopters’ sex or to their sexual orientation. So, in principle, it is possible for a single homosexual person to adopt a child. However, homosexual couples do not have the chance to be monitored by the social service in charge. According to articles 1545 et seq. Civil Code the same person’s adoption by more people at the same time is not possible unless they are married. Given the fact that in Greece same-sex marriage is not permitted, there is no possibility for a child’s adoption by a homosexual couple. In view of the above, there is a clear need for modernization of Family Law regarding the protection of the homosexuals’ rights as an attempt to cope up with contemporary social facts.